2021
DOI: 10.1021/acsaelm.1c00361
|View full text |Cite
|
Sign up to set email alerts
|

Large Damping-like Spin–Orbit Torque and Improved Device Performance Utilizing Mixed-Phase Ta

Abstract: The β phase of Ta is known to exhibit higher spin Hall efficiency compared to other heavy metals such as Pt. However, the larger resistivity of β-phase Ta leads to higher power consumption for spin–orbit torque (SOT)-based devices. In this work, we measure the efficiency of damping-like torque and field-like torque in Ni80Fe20/Ta using spin-torque ferromagnetic resonance technique. We report a larger damping-like torque efficiency of −(0.52 ± 0.01) for Ni80Fe20/Ta with low-resistive mixed (α + β)-phase Ta, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 61 publications
3
23
0
Order By: Relevance
“…The variation in the g ↑↓ is due to the phase fraction of α-Ta and β-Ta. It is worth noting here that the recent works by Bansal et al 23 and Kumar et al 32,58 have also reported similar kinds of observations due to the (α + β)-Ta phase. However, theoretical studies on HM structure dependent spin-mixing conductance are elusive and therefore, it will attract great interest in the community to further dig into using first principle studies.…”
Section: Effect Of the Seedsupporting
confidence: 80%
See 1 more Smart Citation
“…The variation in the g ↑↓ is due to the phase fraction of α-Ta and β-Ta. It is worth noting here that the recent works by Bansal et al 23 and Kumar et al 32,58 have also reported similar kinds of observations due to the (α + β)-Ta phase. However, theoretical studies on HM structure dependent spin-mixing conductance are elusive and therefore, it will attract great interest in the community to further dig into using first principle studies.…”
Section: Effect Of the Seedsupporting
confidence: 80%
“…From the observed θ SH values, it is evident that spin to charge conversion efficiency is directly correlated with the phase of Ta and the estimated θ SH values are in good agreement with the reported values. 32 The enlarged spin Hall angle in the Py/Ta phase has low longitudinal resistance due to the presence of a mixed phase where the major contribution comes from extrinsic mechanisms such as skew scattering and side jump scattering as reported by Kumar et al 23,32,58 The crystalline Py can enhance the θ SH by enlarging the interfacial symmetry break-ing at the Py/Ta interface. Therefore, the key reason for the relatively large θ SH observed in the Py/(α + β)-Ta phase is due to the combined effect of low longitudinal resistance and the enhanced interfacial symmetry breaking.…”
Section: Nanoscale Papermentioning
confidence: 91%
“…For comparison of the spin-to-charge conversion efficiency of these ML TMDs with traditional 3D HMs, we also calculate the so-called pseudo spin Hall angle (θ PSH ) as [17] θ PSH = 2λ IREE /t (6) where t denote the thickness of ML TMDs. In the above equation, the thickness of the TMD is assumed to be less than the spin diffusion length [60].…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has focused on utilizing spin-orbit interaction of heavy metal (HM) and FM heterostructures for spin-to-charge conversion. [3][4][5][6] This has led to a growing field of spin-orbitronics in which coupled interaction of spin and orbital momentum of the electron is employed for interplay between charge and spin currents [5,7]. When an electric current is passed through the HMs with strong spin-orbit coupling (SOC), it produces a transverse spin current due to the spin Hall effect (SHE) [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the role played by SOT-related phenomena in spintronics research, searching for materials with a high SOT efficiency (a rigorous definition will be given below) is naturally at the center stage. Various means have been utilized in such a searching process: a high SOT efficiency can be achieved by varying the composition/thickness/crystal structure of the HM layer or the oxygen content of the magnetic or nonmagnetic (NM) layer. , However, efficient tuning of the SOT efficiency in a given material is not straightforward. This is where materials with magnetic phase transitions (MPTs) may be of assistance: the SOT efficiency may depend sensitively on the magnetic ordering across the transition, and the transition itself can be continuously and reversibly tuned by various control parameters, e.g., temperature, magnetic field, and electric field …”
mentioning
confidence: 99%